2011
DOI: 10.14701/kjhbps.2011.15.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Diabetes after Distal Pancreatectomy: Incidence Rate and Risk Factors

Abstract: PurposePancreatectomy can impair production of endocrine and exocrine hormones. In this study, we evaluated: 1) the incidence rate of diabetes in patients undergoing distal pancreatectomy; 2) the correlation between the occurrence of pancreatic diabetes and the extent of the resected pancreas; and 3) factors associated with the development of pancreatic diabetes.MethodsWe retrospectively reviewed the cases of 26 patients who could be compared in abdominal computed tomography before and after distal pancreatect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
10
3
1
Order By: Relevance
“…Over 80% of cases have mutations in the pancreatic transcription factor genes GATA6 and PTF1A. De Franco et al 14 Baumeister et al15 Kim et al16…”
mentioning
confidence: 99%
“…Over 80% of cases have mutations in the pancreatic transcription factor genes GATA6 and PTF1A. De Franco et al 14 Baumeister et al15 Kim et al16…”
mentioning
confidence: 99%
“…It is acknowledged that surgical trauma leads to a local increase of inflammatory cytokines [ 36 ]. Interestingly, hTERT-MSC infusion attenuated the transcription of IFN-γ and TNF-α at the surgical site.…”
Section: Resultsmentioning
confidence: 99%
“…Because the resected parenchymal volume is smaller with central pancreatectomy than distal pancreatectomy, postoperative pancreatic function is expected to be better after central pancreatectomy. The incidence rate of new-onset diabetes ranges from 9% to 19.2% after distal pancreatectomy [10,11]. It was reported that the incidence rate of new-onset diabetes/impaired glucose tolerance was 0% after central pancreatectomy versus 16% after spleen-preserving distal pancreatectomy [12], while another study found rates of 14% after central pancreatectomy and 46% after distal pancreatectomy [13].…”
Section: Conflict Of Interestmentioning
confidence: 99%